PONDERABLE ACHIEVEMENT OF UKRAINIAN TERMINOGRAFII Golyanych M.I., Stefurac R.I., Babiy I.O. Dictionary of linguistic terms: lexicology, phraseology, lexicography / after the release M.I. Golyanych. – Ivano-Frankivs’k: Simic, 2011. – 272 s. - Pena , L. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Attention on the practical value of the dictionary out of linguistic terms given by the Ivano-Frankivs’k research workers is accented in a review, and also on his scientific value, that it is conditioned by the necessities of modern Ukrainian lexicography.